Analisis Tanggung Jawab Perbankan Syariah Dalam Meningkatkan UMKM Di Kota Medan - Putri, Eka Khayana; Rokan, Mustapa Khamal; Syahbudi, Muhammad (Universitas Islam Negeri Raden Intan, 2023)
This study aims to identify and examine the responsibilities, as well as the difficulties encountered and the efforts made by PT Bank Syariah Indonesia, Tbk KC Medan S.Parman to increase MSMEs in Medan City. Qualitative research methods are used in this study. Both primary and secondary data sources. The results of the study show that PT Bank Syariah Indonesia, Tbk KC Medan S.Parman is very responsible and contributes actively to the National Economic Recovery (PEN). Has provided financing of up to IDR 36 billion to more than 180 customers in Medan City for various MSME sectors from 2021 to 2022. Access to capital and financing. The obstacles encountered are the lack of innovation, and the lack of business licenses. Efforts are being made to develop MSME centers in Aceh, Yogyakarta and Surabaya, Indonesia, offering the KUR Cluster Program and a number of KUR products, including KUR BSI, KUR BSI Small, KUR BSI Micro, and KUR BSI Super Micro, to help MSMEs get access to capital and financing. In order to advance MSMEs in Indonesia.